Winter stratospheric extreme events impact European storm damage - Hilla Afargan-Gerstman; Daniela I. V. Domeisen (Communications Earth & Environment)
Abstract Extreme stratospheric events, such as sudden stratospheric warmings or strong polar vortex events, can have a persistent influence on winter surface weather. While these changes often lead to shifts in extratropical cyclone tracks and increased risk of extreme winds, flooding, or heavy snowfall, there has been no systematic effort to quantify their associated impacts with respect to stratospheric forcing. Here we establish the connection between stratospheric extreme events and midlatitude storms in the Euro-Atlantic region using reanalysis of the European Centre for Medium-Range Weather Forecasts and impact datasets. We show that storm-related hazards in northern Europe occur more frequently following strong vortex events than after sudden stratospheric warmings. Moreover, stratospheric forcing shapes the geographic pattern of storm impacts. Quantifying these connections - from precursors to hazards and impacts - can enable earlier warnings for society and for decision-makers in sectors such as emergency preparedness, public health, energy, and water management.